LRRK2 is a component of granular alpha-synuclein pathology in the brainstem of Parkinson's disease. - Alegre-Abarrategui, J; Ansorge, O; Esiri, M; Wade-Martins, R (2008)
Classical Parkinson's disease (PD) is characterized by the appearance of Lewy bodies (LBs) in affected brain regions, showing mostly compact alpha-synuclein deposition, in contrast with punctate or granular deposition, hypothesized to represent early stages of aggregation. Leucine-rich repeat kinase 2 (LRRK2) is the commonest mutated gene in inherited and idiopathic PD. LRRK2 mutation carriers display a diverse neuropathology, including alpha-synuclein and tau inclusions, suggesting an upstream role for LRRK2 in protein aggregation. We studied LRRK2 expression throughout the normal human brain with three different antibodies. We also examined the pattern of LRRK2 expression in relation to alpha-synuclein aggregation and LB formation in the brainstem of sporadic LB disease. Physiological LRRK2 expression was not restricted to regions preferentially affected in PD and LRRK2 often localized to the nuclear envelope in addition to the known cytoplasmic expression. In PD, we were able to consistently detect LRRK2 in the halo of a minority (approximately 10%) of nigral LBs using three different antibodies. Only one antibody detected LRRK2 in the core of approximately 80% of classic LBs. In the lower brainstem, most notably in the dorsal motor nucleus of the vagus, we found previously unrecognized LRRK2 labelling of complex globular lesions, filled with LB-like matter showing a punctate or granular staining for alpha-synuclein. This was often accompanied by strong LRRK2 expression within dystrophic neurites. Our findings confirm widespread physiological LRRK2 expression in the human brain and suggest an association of LRRK2 with possible early-stage alpha-synuclein pathology in the brainstem of PD.